Digital Transformation of English Language Learning Through Artificial Intelligence Chatbots: Teacher and Student Perspectives in Central Aceh - Astuti, Widya (Journal of English Language and Education, 2026)
This research aims to examine the students’ and teachers’ perspectives in Aceh Tengah regarding the digital transformation of English language learning through Chatbot AI. Descriptive qualitative design was employed and the data gather through semi structure interview with 4 English teachers and 12 senior high school students in Aceh Tengah. The findings indicate that digital technology, including Chatbot AI, has been used as a supporting tool in English language learning, particularly to assist in understanding materials, completing assignments, and expanding students’ knowledge. Students perceive Chatbot AI as beneficial due to its ease of use, speed, and clarity of information, while teachers view it as an additional learning resource that should be used wisely with supervision and verification of information. Nevertheless, the use of Chatbot AI remains limited due to facility constraints, uneven internet access, school policies restricting device usage, and differences in students’ English proficiency levels. The conclusions and recommendations of this study are expected to contribute to policymakers, educators, application developers, and researchers in enhancing understanding of the impact of Chatbot AI on English language learning.